(untitled) (BIOPROSPEK: Jurnal Ilmiah Biologi, 2015)
[Artikel telah ditarik] The fertility of a rooster is not only influenced by motility, viability and DNA integrity of the spermatozoa but it is determined by the morphological integrity of the spermatozoa. This study objectives to determine the morphological and morphometric spermatozoa of nunukan rooster, one of Indonesian germplasm. Rooster’s cement was collected using dorso-abdominal massage method. The cement was stained with a combination of eosin Nigrosin. The stained cement was used to observe the morphology and measurement of the main parameters. The morphological was evaluated using a microscope with a magnification of 100x as many as 100 spermatozoa. The spermatozoa morphometric were analyzed using the Raster Image program and its were identified the head dimension, the head length and width, the mid-piece length, the tail length, and the ratio of the head and tail. A nunukan rooster spermatozoon in average has total length of 86.724 ± 12.496 μm with a head length, the mid-piece length, the tail length is 12.766±2.307 μm, 4.220±1.127 μm, and 75.738 ± 9.061 μm, respectively, while the head width is 1.391±0.244 μm, and the the head: the tail ratio is 1: 5.9. The morphologically normal percentage is 80.50 ± 9.40 %. In conclusion, the characteristics spermatozoa of nunukan rooster due to morphology, morphometric, and morphologically normal percentage aspects are within the range of other types of rooster in many previous studies.